Optimalisasi Potensi Sumber Daya Lokal, Infrastruktur, dan Digitalisasi Melalui Pemberdayaan Masyarakat Untuk Meningkatkan Kualitas Serta Place Branding Desa Duano - Pakaya, Srie Isnawaty; Asnawi, Melan Angriani; Modanggu, Ibrahim S. (Universitas Negeri Gorontalo, 2025)
This community service program was carried out in Duano Village, Suwawa Tengah Sub-district, Bone Bolango Regency, Gorontalo Province, aiming to optimize local resource potential, strengthen community digital literacy, and develop village place branding strategies. The implementation method used a participatory approach consisting of preparation, implementation, evaluation, and follow-up stages. Activities included mapping local resources, providing digital literacy training for MSMEs, conducting workshops on product innovation based on local resources, and developing a digital platform in the form of a village website. The results showed a significant improvement in community knowledge and skills in utilizing digital technology, particularly in MSME product marketing. The innovation of “Bika Singkong Duano” was successfully developed as a form of downstream processing of local agricultural products, while the village website became an effective digital promotion medium to introduce Duano Village’s superior products, culture, and tourism potential. This program not only had a positive impact on improving human resource quality and MSME competitiveness but also strengthened the village’s identity in the digital era. As a follow-up, continuous mentoring and proper management of the digital platform are needed to ensure the sustainability of these achievements and their contribution to the community’s economic and social development.